The Impact of “Learning Organizations” on Innovation: The Mediating Role of “Employee Resilience” and Work Engagement - Sami Mohammad; Mustafa Sağsan; Harun Şeşen (SAGE Open)
This study investigates the characteristics that may affect an organization’s capacity for innovation. We explored the effects of learning organizations on creativity through employee resilience and work engagement, utilizing a standardized questionnaire administered to 430 Jordanian bank workers. The data were analyzed using WarpPLS, employing partial least squares structural equation modeling (PLS-SEM) (version 8.0). Our findings reveal a significant and positive influence of “learning organization” on innovation, “work engagement,” and worker resilience. Furthermore, employee resilience and job engagement significantly and positively impact innovation. Additionally, employee resilience and workplace engagement significantly mediate the relationship between learning organizations and innovation. This study’s theoretical implications highlight how organizational learning theory can be used to enhance organizational creativity. A complete strategy that considers both organizational strategies and human aspects is necessary to promote innovation.